Challenges and Opportunities in the Philippine Blue Economy: A Systematic Literature Review - Campos, Karl; Masita, Elly Dwi; Agustina, Heni (Universitas Nahdlatul Ulama Surabaya, 2024)
Blue Economy is an emerging concept that focuses on the sustainable utilization of ocean resources. The Philippines, being an archipelagic country, has a vast potential for Blue Economy development. This paper aims to provide a comprehensive review of the Blue Economy in the Philippines. The study examines the current state of the Blue Economy, identifies the challenges, and presents strategies for sustainable development. The review of literature includes research articles, policy documents, and relevant reports. The study used a qualitative research design, relying on secondary data analysis. The results show that the Philippines has significant potential for Blue Economy development, but the challenges include overfishing, pollution, and climate change. The paper concludes that sustainable development of the Blue Economy in the Philippines requires coordinated efforts from various stakeholders, including government, private sector, civil society, and the international community. This novel review of the emerging blue economy concept in the Philippines emphasizes its opportunities, challenges, and the need for multi-stakeholder collaboration for sustainable development, supported by an extensive analysis of diverse literature sources.